2019
DOI: 10.1002/adtp.201900053
|View full text |Cite
|
Sign up to set email alerts
|

Advanced NIR‐II Fluorescence Imaging Technology for In Vivo Precision Tumor Theranostics

Abstract: As a cutting-edge imaging technology, fluorescence imaging in the second near-infrared (NIR-II, 1000-1700 nm) window has attracted tremendous attention. Compared to the classical fluorescence imaging in the visible (400-650 nm) and NIR-I (650-950 nm) window, the NIR-II fluorescence imaging greatly improves photon penetration in living bodies with high fidelity due to its minimized tissue absorption, scattering, and autofluorescence. It is considered to be the next-generation intravital fluorescence imaging tec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(29 citation statements)
references
References 70 publications
0
29
0
Order By: Relevance
“…2a). [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28] However, the uorescence efficiency (F) decreases remarkably with wavelength (l), especially in low energy bandgap NIR-II materials, as intramolecular motions around the single or double bond result in dominant non-radiative relaxation dynamics (Fig. 2b).…”
Section: Introductionmentioning
confidence: 99%
“…2a). [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28] However, the uorescence efficiency (F) decreases remarkably with wavelength (l), especially in low energy bandgap NIR-II materials, as intramolecular motions around the single or double bond result in dominant non-radiative relaxation dynamics (Fig. 2b).…”
Section: Introductionmentioning
confidence: 99%
“…NIR-II imaging has great application potential in tumor angiography because it can not only accurately display the abnormal tumor vascular morphology and the changes associated with tumor growth, but also provides an important reference for the judgment of tumor metastasis and the evaluation of cancer therapeutic effect. [92] For instance, Hao and coworkers reported that PAA-Ln-NRs (poly(acrylic acid) modified nanorods with Gd/Yb/Er/Ce codoped NaLnF 4 core, Ln = Y, Yb, Lu) showed strong NIR-IIb emission at 1525 nm, and detected abundant blood vessels inside and outside the primary tumor with high spatial resolution (41 µm), as well as identifying small necrotic areas on the epidermis (LP: 1500 nm). Moreover, PAA-Ln-NRs successfully recognized tiny metastases with a size of 2 mm and revealed tumor angiogenesis in metastases with a size of 4 mm (Figure 5a).…”
Section: Tumor Vascular Imagingmentioning
confidence: 99%
“…The synthetic routes and characterization of the three molecules associated with intermediates were shown in the supplementary material [Scheme (1-3), Figures (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)]. Traditionally, most NIR-II fluorophores are derived from D-A-D structures.…”
Section: Molecular Synthesis and Designmentioning
confidence: 99%
“…4,5 Fluorophores emitting in the near-infrared II (NIR-II, 1000-1700 nm) region have received increasing attention because of its merits for having increased tissue penetration, improved spatial resolution and high signal-to-background ratio. [6][7][8][9][10][11][12][13][14][15] To date, outstanding achievements have been obtained by inorganic materials, attaining enhanced brightness for biomedical applications. [16][17][18][19][20] However, these inorganic materials generally suffer from potentially long-term toxicity.…”
Section: Introductionmentioning
confidence: 99%